Petrofabric development during experimental partial melting and recrystallization of a mica‐schist analog. (17th October 2015) - Almqvist, Bjarne S. G.; Biedermann, Andrea R.; Klonowska, Iwona; Misra, Santanu
Abstract: Magnetic properties and the anisotropy of magnetic susceptibility (AMS) present promising methods to track mineral orientation and petrofabric in rocks that have undergone partial melting. In order to better understand the source of the magnetic signal in these types of rocks, the interpretation of field observations may be integrated with laboratory experiments, designed to recreate conditions of partial melting. A set of experiments is presented in this study, where synthetic foliated quartz‐muscovite aggregates undergo partial melting at 300 MPa hydrostatic confining pressure and 750°C. Magnetic properties and AMS are measured before and after partial melting. Prior to partial melting, the synthetic aggregate shows a compaction‐related oblate magnetic fabric, dominated by paramagnetic muscovite that contains small amounts of iron. Post experiment samples show neoblasts that crystallize from incongruent melt reactions. Most notably for the magnetic fabric, the breakdown of muscovite results in growth of secondary phases of Fe‐bearing spinel and biotite. Isothermal remanence acquisition and temperature dependence of susceptibility indicate that the spinel is magnetite. The degree of magnetic anisotropy reduces significantly after partial melting, but notably the orientation of the principal axes of susceptibility mimics the AMS of the original quartz‐muscovite aggregate. Additionally, the post experiment samples show a relationship between the amount of sample shortening (compaction) and the degree of magnetic anisotropy and susceptibility ellipsoid shape factor. These results suggest that petrofabrics in rocks that undergo partial melting at near hydrostatic pressure conditions may in part be inherited, or mimic, the original petrofabric of a sedimentary or metasedimentary rock. Key Points: We perform laboratory experiments to study petrofabric development during partial melting Petrofabric is in part inherited in the partially melted aggregates A close relationship between compaction and magnetic fabric development is identified